2023
DOI: 10.12912/27197050/154937
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Land Use and Land Cover Change Using Remote Sensing Techniques and the Precipitation-Vegetation Indexes in Morocco

Abstract: The study of land use and land cover change (LULC) is essential for the development of strategies, monitoring and control of the ecosystem. The present study aims to describe the dynamics of land cover and land use, and specially the impact of certain climatic parameters on the distribution of vegetation and land cover. For this study, multi-temporal remote sensing data are used to monitor land cover changes in Morocco, using a set of Landsat images, including Landsat 7 (ETM+), Landsat 5 (TM), and Landsat 8 (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In the same region, Mohajane et al (2018) studied the vegetation change of Azrou forest with three classes (vegetation of low‐density, moderate‐density and high‐density) using Landsat data and the Maximum Likelihood classification method, which produced an overall accuracy ranging from 66.8% to 99.9%. Ait El Haj et al (2022) obtained an overall accuracy ranging from 80% to 93% in a study of land cover/land use change and vegetation cover distribution in the Moroccan region of Béni Mellal‐Khénifra, based on Landsat images and the Maximum Likelihood classification method. This algorithm provided higher accuracies (100%) in another land cover change study conducted in the Moroccan Western High Atlas (Omdi et al, 2017) using the same data source (Landsat images).…”
Section: Discussionmentioning
confidence: 99%
“…In the same region, Mohajane et al (2018) studied the vegetation change of Azrou forest with three classes (vegetation of low‐density, moderate‐density and high‐density) using Landsat data and the Maximum Likelihood classification method, which produced an overall accuracy ranging from 66.8% to 99.9%. Ait El Haj et al (2022) obtained an overall accuracy ranging from 80% to 93% in a study of land cover/land use change and vegetation cover distribution in the Moroccan region of Béni Mellal‐Khénifra, based on Landsat images and the Maximum Likelihood classification method. This algorithm provided higher accuracies (100%) in another land cover change study conducted in the Moroccan Western High Atlas (Omdi et al, 2017) using the same data source (Landsat images).…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring LULC changes provides comprehensive information on changes in the potential of carbon sequestration of forest land [25].LULC used by Benzougagh et al2023 to evaluate soil susceptibility in the Inaouene watershed [26]. Ait El Haj et al,2022 used LULCC maps to assess the vegetation cover subjected to soil erosion in Lakhdar sub-basin [27].LULC was used in a study focusing on the relationship between LST and urban morphological parameters in Nanjing, China [6]. Zeng et al, 2018 conducted a LULC change study using the Global Forest Change of Hansen to evaluate Highland cropland expansion and forest loss in Southeast Asia in the twenty-first century [28].…”
Section: Introductionmentioning
confidence: 99%
“…Landsat is widely used (Ait El Haj et al, 2023;Cai et al, 2020;Dhaloiya et al, 2023;Milanović et al, 2019) by application of NDVI index (Ozyavuz, et al, 2015;Sonali et al, 2021) and supervised classification (Bispo et al, 2013;Salata, 2021). A study in Benslimane, nearby area, is carried out by Hammouyat et al, using the same process, revealed that the forest is declined by 11.4 % losing nearly 200 ha/year (Hammouyat et al, 2022), andHoussni et al (2018) showed that high formations, low formations, and matorrals have regressed by 62%, 70%, and 49% respectively in the Western Rif region of Morocco (Houssni et al, 2018).…”
Section: Introductionmentioning
confidence: 99%